Pengaruh Insentif, Pelatihan, dan Lingkungan Kerja Terhadap Kinerja Karyawan - Putri, Brenda Yulieta (Nur Science Institute, 2023)
This study aims to determine the effect of incentives, training, and work environment on employee performance at Yarsis Islamic Hospital of Surakarta either partially or simultaneously. This research method is a quantitative method. The population in this study were 287 employees of the Yarsis Islamic Hospital of Surakarta with a total sample of 74 respondents. Data collection was done by using a questionnaire via google form. Data analysis to test the hypothesis using the regression equation, F test, t test, and the coefficient of determination. Based on the results of the analysis, it is known that 1) Incentives have a significant effect on employee performance. This is indicated by the regression coefficient value of 0.114, tcount 20.021 and a significance value of 0.047. 2) Training has a significant effect on employee performance. This is indicated by the regression coefficient value of 0.329, tcount 20.337 and a significance value of 0.022. 3) Work environment has a significant effect on employee performance. This is indicated by the regression coefficient value of 0.432, tcount 40.336 and a significance value of 0.000. 4) Incentives, training, and work environment have a significant effect on employee performance. This is indicated by the Fcount value of 520.133 and a significance value of 0.000.